Psychological impact of cancer on patients in a tertiary care centre: a prospective study - Shafi, Saba; SShah, Manan; Shafi, Junaid; Shah, Momin; Khan, A. W. (International Journal of Research in Medical Sciences, 2019)
Background: Diagnosis of cancer, although physical in nature, has far reaching emotional impact on the person. The study aimed to analyse the psychological impact of cancer on patients with a focus on levels of distress and psychiatric comorbidity. Methods: It was a prospective study conducted on 169 consenting individuals in the department of radiation oncology, SKIMS, Jammu and Kashmir, India, in collaboration with the department of psychiatry, SKIMS medical college, Jammu and Kashmir, India, from November 2013 to January 2015. The NCCN distress thermometer was used to observe the temporal variations in the levels of distress over a period of time. Results: Anxiety disorders (panic disorder, generalized anxiety disorder and post-traumatic stress disorder) were the most common psychiatric disorders diagnosed constituting 59%, followed by depression in 29%. About 12% patients were not diagnosed with any psychiatric ailment. One female patient with anxiety disorder developed acute psychosis. Counselling and psychotherapy provided improvement in 45% patients with cancer. In all, 86.4% required medication during the course of treatment and majority had improvement with it. A mean distress score of 7.73 was seen before, 8.29 during and 7.66 after treatment. Conclusions: Cancer bore a significant impact on the psychological bearing of patients, ranging from anxiety disorder, post-traumatic stress disorder, depression to psychosis. Hence there is a need for monitoring psychological symptoms in cancer patients and development of appropriate psycho-oncology services.